Co-creation of a training for community health workers to enhance skills in serving LGBTQIA+ communities - Kitzie, Vanessa; Smithwick, Julie; Blanco, Carmen; Green, M. Greg; Covington-Kolb, Sarah (Frontiers in Public Health, 2023)
This paper describes creating and implementing a 30-hour LGBTQIA+ specialty training for community health workers (CHWs). The training was co-developed by CHW training facilitators (themselves CHWs), researchers with expertise in LGBTQIA+ populations and health information, and a cohort of 11 LGBTQIA+ CHWs who theater tested and piloted the course. The research and training team collected cohort feedback through focus groups and an evaluative survey. Findings stress the importance of a curriculum designed to elicit lived experiences and informed by a pedagogical framework centered on achieving LGBTQIA+ visibilities. This training is a vital tool for CHWs to foster cultural humility for LGBTQIA+ populations and identify opportunities to support their health promotion, especially considering their limited and sometimes absent access to affirming and preventative healthcare. Future directions include revising the training content based on cohort feedback and adapting it to other contexts, such as cultural humility training for medical and nursing professionals and staff.